Hipolito Unanue and thePeruvian epidemiology discourse building process - Murillo, Juan Pablo (2005)
This essay is a first approximation to the study of Hipolito Unanue’s thinking influence on the Peruvian epidemiology discourse construction. After describing general aspects of Unanue’s thought on the processes of disease propagation, we discuss how at the beginning of the XX century, in middle of the debate on the community problems and the various possibilities of the nation’s development, different authors retake Unanue’s ideas, who had already been raised up as a cultural hero of the medical community. We analyze his influence in the work of intellectuals like Paz Soldan, Olaechea and Lastres analyzing the diverse particularities of their thinking decodifying process and how this allowed the development of an identity process linked to the making of a ‘Peruvian conscience’, that is, of a particular way of seeing and transforming the world. This systemic way of approaching Peru’s complexity is one of the characteristics of the initial development of Peruvian epidemiology, where History, Geography, Sociology, Anthropology, and Eugenics converge to outline explanations proper to the diseases propagation processes in Peru.